Exploring the effects of carrier oil type on in vitro bioavailability of β-carotene: A cell culture study of carotenoid-enriched nanoemulsions. (December 2020) - Xia, Ziyuan; Han, Yanhui; Du, Hengjun; McClements, David Julian; Tang, Zhonghai; Xiao, Hang
Abstract: β-carotene was encapsulated in either olive oil or flaxseed oil-in-water nanoemulsions, and it's in vitro bioaccessibility and bioavailability were determined in a simulated gastrointestinal digestion model (mouth, stomach and small intestine) combined with a Caco-2 cell monolayer model. Nanoemulsions fabricated from both types of oils significantly increased the in vitro bioaccessibility and bioavailability of β-carotene. Olive oil, however, was digested more efficiently, which generated more free fatty acids capable of forming mixed micelles. Furthermore, the mixed micelles stimulated the formation of lipoprotein particles (chylomicrons and very low-density lipoproteins), which are the transcellular carriers of β-carotene in the intestinal epithelium, leading to an increase in bioavailability. Interestingly, olive oil led to the formation of larger chylomicrons than flaxseed oil, suggesting that fatty acid type impacts the nature of the lipoprotein particles formed after lipid digestion. Highlights: Olive oil and flaxseed oil-based nanoemulsions containing β-carotene were fabricated. Both nanoemulsions enhanced β-carotene bioaccessibility and bioavailability in vitro. Olive oil-based nanoemulsion resulted in higher bioaccessibility and bioavailability.